Haplótipos da adiponectina, excesso de peso e alterações na homeostasia glicêmica em adolescentes da Grande Vitória - Fonseca, Simone Rodrigues da (2018)
Obesity is a chronic inflammatory disease characterized by excess fat and has been increasing significantly among children and adolescents leading to various complications in childhood and adulthood, such as: systemic arterial hypertension, impaired glucose intolerance, dyslipidemia and type 2 diabetes. A number of factors contribute to childhood obesity and may be: genetic, environmental, and behavioral. Studies have investigated genetic factors predisposing to obesity, although these factors are still poorly understood. The genes that are candidates for predisposition to obesity are related to the regulation of hunger, energy balance, lipid metabolism and glucose; and differentiation of adipocytes. In this context, the adiponectin gene (ADIPOQ) that regulates insulin sensitivity, and is involved in the inflammatory response and regulation of energy balance, represents an interesting opportunity to identify the primary genetic determinants involved in the susceptibility to obesity and diabetes in children and adolescents, since these are one of the main target groups for strategies for research, prevention and control of overweight and obesity. The objective of this study was to analyze the frequencies of genotypes and / or haplotypes to verify the polymorphism in the ADIPOQ gene and its association with the susceptibility to excess weight and alterations of the glycemic homeostasis of adolescents enrolled in public schools in the Metropolitan Region of Vitória-ES, from a representative sample of the study "Prevalence of overweight and obesity in adolescents in the state of Espirito Santo and his association with some variables of the metabolic syndrome "were randomly included in the genetic study. For classification of nutritional status, the body mass index / age (BMI / I) index was considered in z score. Genomic DNA was extracted from peripheral blood samples. For the ADIPOQ gene, the DNA was amplified by Taqman methodology. Data from the individuals related to race, gender, age, BMI / I, glycemia, insulin and HOMA-IR (Homeostasis Model Assessment-Insulin Resistance) were analyzed in SPSS software version 23.0. A total of 350 adolescents aged 10-14 years were investigated, divided into two groups: overweight (n = 109) and no overweight (n = 241), with fourth SNPs in the ADIPOQ gene rs17300539 (-11391 G); 266729 (- 11377C); rs2241766 (45T> G) and rs1501299 (276G> T). For SNP (+ 45T> G), we observed association of genotypes with excess weight (p = 0.04), and association for HOMA β% (p = 0.028). Associations of the ADIPOQ gene haplotypes in the coding region of the ADIPOQ + 45T> G and + 276G> T gene were associated with increased serum glucose levels. We conclude that polymorphism and / or haplotypes TG in the ADIPOQ gene is related to susceptibility to excess weight and changes in adolescent glycemic homeostasis in an age group between 10 - 14 years.